WAYS TO IMPROVE LOCAL BUDGET REVENUE GROWTH - Kudaybergenova Guzal (American Journals, 2024)
Ways to improve the increase of local budget revenues are considered. Factors affecting tax revenues of local budgets are analyzed. Also, the tax rates collected from the income of individuals in the countries of the world were comparatively analyzed.
Keywords: Budget revenues, tax, local budget, tax policy, investment environment.